2020
DOI: 10.1177/0363546520905863
|View full text |Cite
|
Sign up to set email alerts
|

Repair With Dynamic Intraligamentary Stabilization Versus Primary Reconstruction of Acute Anterior Cruciate Ligament Tears: 2-Year Results From a Prospective Randomized Study

Abstract: Background: Anterior cruciate ligament (ACL) repair has once again become a focus of research because of the development of new techniques. Purpose/Hypothesis: The purpose was to compare the functional results and recurrent instability rates in patients undergoing ACL repair with dynamic intraligamentary stabilization (DIS) versus primary ACL reconstruction (ACLR) for acute isolated ACL tears. The hypothesis was that functional results and knee joint stability after ACL repair with DIS would be comparable with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
115
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(130 citation statements)
references
References 47 publications
11
115
2
2
Order By: Relevance
“…The arthroscopic ACL repair technique with the most experimental and clinical data available is DIS [ 32 , 33 , 34 , 35 , 36 ]. Although several authors reported functional results comparable to our cohort, Ahmad et al reported low DIS survival rates (of only 70% at 5-year follow-up) and Osti et al reported a high rate of recurrent instability (of up to 17.5%) [ 22 , 32 , 35 , 37 , 38 ]. While Ahmad et al concluded that they were lacking evidence of the ideal surgical candidate during patient enrolment and stricter indications would have likely resulted in an overall better outcome, first randomized clinical trials show that functional results and clinical failure of DIS are comparable to ACL reconstruction [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The arthroscopic ACL repair technique with the most experimental and clinical data available is DIS [ 32 , 33 , 34 , 35 , 36 ]. Although several authors reported functional results comparable to our cohort, Ahmad et al reported low DIS survival rates (of only 70% at 5-year follow-up) and Osti et al reported a high rate of recurrent instability (of up to 17.5%) [ 22 , 32 , 35 , 37 , 38 ]. While Ahmad et al concluded that they were lacking evidence of the ideal surgical candidate during patient enrolment and stricter indications would have likely resulted in an overall better outcome, first randomized clinical trials show that functional results and clinical failure of DIS are comparable to ACL reconstruction [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…Although several authors reported functional results comparable to our cohort, Ahmad et al reported low DIS survival rates (of only 70% at 5-year follow-up) and Osti et al reported a high rate of recurrent instability (of up to 17.5%) [ 22 , 32 , 35 , 37 , 38 ]. While Ahmad et al concluded that they were lacking evidence of the ideal surgical candidate during patient enrolment and stricter indications would have likely resulted in an overall better outcome, first randomized clinical trials show that functional results and clinical failure of DIS are comparable to ACL reconstruction [ 37 , 38 ]. Although the understanding of the ideal surgical candidate for ACL repair has evolved over the past few years and critical patient selection was routinely performed in the reported cohorts, no randomized controlled trial comparing SA and ACL reconstruction has yet been performed [ 10 , 35 ].…”
Section: Discussionsupporting
confidence: 73%
“…compared primary ACL repair with DIS to primary ACL reconstruction and found significantly increased anterior tibial translation (ATT) in the DIS group but similar failure rates between the two groups. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Despite better patient selection and advances in repair techniques, the risk of failure after isolated suture repair of the ACL remains a concern. 8 Intra-articular augmentation has been proposed to protect the repair during the healing period. 6,9 The originality of the technique described here consists of the use of a single-strand gracilis graft as a "biological" internal brace for intra-articular augmentation of the repair and as an anterolateral graft to protect the repair during the healing phase.…”
Section: Discussionmentioning
confidence: 99%